Advances in the application of computational fluid dynamics in cardiovascular flow. Issue 1 (31st December 2023) - Kumar, Nitesh; A, Ganesha; H, Girish; Kumar, Shiva; Shenoy B, Gowrava
Abstract: Computational Fluid Dynamics (CFD) plays an important role in assessment of genesis and prognosis of atherosclerosis and as a promising tool for risk stratification. CFD is widely used by a majority of the researchers, although, many experimental studies show that the results obtained by CFD are inconsistent with the physio-pathological manifestations, which is mainly due to inconsistent definition of parameters, limited data availability and extreme complexity and heterogeneous behavior of plaque growth and its rupture. In this review, the results obtained by Computational Fluid Dynamics are summarized and an attempt is made to deduce the broad causes of various errors and possible solutions.